Economic Feasibility of Power Supply Using Hybrid System for a Hotel in Cold Climate - Agabalaie Fakhim, Hamed; Sarir, Mohammad Faraji (International Journal of Energy Economics and Policy, 2017)
Today, renewable resources are used growingly due to environmental impact of fossil fuels. Solar and wind energies are of the largest renewable resources which are increasingly used to generate the power. In this paper, firstly, power and speed of wind and potential of solar radiation in Iran, especially in Tabriz, were examined. Then, using this analysis, an appropriate hybrid system was provided to meet the energy consumption of a hotel in Tabriz Town which is not connected to the electricity network. For this, firstly, thermal load of heating and cooling required for a building in Tabriz Town was accurately calculated by Energyplus software and then, four hybrid system scenarios were determined and examined by Homer software. The results of data analysis of economic feasibility showed that wind-diesel hybrid system with a storage battery is the most efficient system for power supply of a hotel. Keywords: Energy Plus, hybrid systems, Homer, feasibility JEL Classifications: Q4, Q54